2016
DOI: 10.1158/0008-5472.can-15-1490
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells Express Bruton's Tyrosine Kinase and Can Be Depleted in Tumor-Bearing Hosts by Ibrutinib Treatment

Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous group of immature myeloid cells that expand in tumor bearing hosts in response to soluble factors produced by tumor and stromal cells. MDSC expansion has been linked to loss of immune effector cell function and reduced efficacy of immune-based cancer therapies, highlighting the MDSC population as an attractive therapeutic target. Ibrutinib, an irreversible inhibitor of Bruton’s tyrosine kinase (BTK) and IL2-inducible T-cell kinase (ITK), is in clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(156 citation statements)
references
References 50 publications
3
153
0
Order By: Relevance
“…Sagiv-Barfi and colleagues (16) demonstrated that ibrutinib in combination with anti-PD-L1 antibody provoked strong host T-cell-mediated antitumor activity against various tumor types, including triple-negative breast cancer, which led to high response rates and suppression of metastases. Others have reported ibrutinib modulation via BTK inhibition of myeloid-derived suppressor (17) or mast cells (18) in various solid tumor models. Our enzymatic and cellular assays indicated that the potential for such activities based on ITK and BTK inhibition were relatively unique for ibrutinib compared with other ERBB kinase family inhibitors studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sagiv-Barfi and colleagues (16) demonstrated that ibrutinib in combination with anti-PD-L1 antibody provoked strong host T-cell-mediated antitumor activity against various tumor types, including triple-negative breast cancer, which led to high response rates and suppression of metastases. Others have reported ibrutinib modulation via BTK inhibition of myeloid-derived suppressor (17) or mast cells (18) in various solid tumor models. Our enzymatic and cellular assays indicated that the potential for such activities based on ITK and BTK inhibition were relatively unique for ibrutinib compared with other ERBB kinase family inhibitors studied.…”
Section: Discussionmentioning
confidence: 99%
“…Ibrutinib in combination with anti-PD-L1 antibody was shown to provoke strong host T-cell-mediated antitumor activity against various tumor types (16). Inhibition of BTK by ibrutinib has been suggested to be beneficial in some models by modulating myeloid-derived suppressor cells (17) and mast cells (18). Thus, if ibrutinib has clinically meaningful HER2-targeting activity, its effectiveness could be augmented by such modulation of the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…The clinically approved cancer therapeutics ibrutinib and sunitinib inhibited tyrosine kinases present in MDSCs and prevented MDSC generation, migration, and function in several murine tumor models (64,145).…”
Section: Direct Targeting Of Mdscs In Vivomentioning
confidence: 99%
“…89 In addition, in a report from Stiff et al on the effects of ibrutinib treatment on MDSCs, which express BTK, ibrutinib inhibited BTK phosphorylation. 90 Together with reduced cell migration and inhibition of in vitro MDSC generation, ibrutinib treatment also reduced MDSCs in spleen and EMT6 murine mammary tumors. Further, ibrutinib treatment reduced MDSCs in a melanoma model in a BTK-dependent fashion.…”
Section: Ibrutinib In T Cells and Other Immune Cellsmentioning
confidence: 99%